2021
DOI: 10.1007/s10571-021-01081-8
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Dexamethasone Treatment Induces Sex-dependent Upregulation of NTPDase1/CD39 and Ecto-5ʹ-nucleotidase/CD73 in the Rat Fetal Brain

Abstract: Dexamethasone (DEX) is frequently used to treat women at risk of preterm delivery, but although indispensable for completion of organ maturation in fetus, antenatal DEX treatment may exert adverse sex-dimorphic neurodevelopmental effects. Literature ndings implicated oxidative stress in adverse effects of DEX treatment.. Purinergic signalling is involved in neurodevelopment, and controled by ectonucleotidases, among which in the brain are most abundant ectonucleoside triphosphate diphosphohydrolase 1 (NTPDase1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…The fact that direct-and second-hand cigarette smoke exposure leads to significant deregulation of CD39 in the lung tissue of mice and rats (Kratzer et al, 2012;Lazar et al, 2016), suggests that combustion products of tobacco directly affect CD39 in respiratory epithelial cells, whereas compounds crossing the air-blood barrier of the lung do not affect placental CD39. Data on sex-dependent differences in CD39 expression is very limited, but suggest that antenatal dexamethasone treatment induces sex-specific upregulation of CD39 in rat brains more prominently in males (Manojlovic-Stojanoski et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that direct-and second-hand cigarette smoke exposure leads to significant deregulation of CD39 in the lung tissue of mice and rats (Kratzer et al, 2012;Lazar et al, 2016), suggests that combustion products of tobacco directly affect CD39 in respiratory epithelial cells, whereas compounds crossing the air-blood barrier of the lung do not affect placental CD39. Data on sex-dependent differences in CD39 expression is very limited, but suggest that antenatal dexamethasone treatment induces sex-specific upregulation of CD39 in rat brains more prominently in males (Manojlovic-Stojanoski et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Also, Quast et al demonstrated that adenosine formed by CD73 inhibits cardiac inflammation and fibrosis in transverse aortic constriction (TAC)-induced heart failure [ 14 ]. Recent studies have shown a sex-specific immuno-metabolic and neuromodulatory response of the CD73/ adenosine axis in the brain and liver [ 19 , 20 ]. However, the sex difference on the CD73/ adenosine axis during cardiac dysfunction is poorly elucidated.…”
Section: Introductionmentioning
confidence: 99%